2020
DOI: 10.3390/land9060188
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Process of Academic Education on Differences in Landscape Perception between the Students of Environmental Engineering and Civil Engineering

Abstract: As technical and technological progress takes place, there is dissonance between teaching good engineering and technological techniques and respect for the landscape. Engineering students are educated to act as initiators and performers of activities that change space. The purpose of this study is to answer question regarding how the engineering students recognize problems related to shaping the landscape. In the years 2012–2015, surveys were conducted in a group of 274 students of the University in their fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…Moreover, due to insufficient visits and excursions, the effect of traditional landscape education is poor. Students aspire to have a new technology incorporated into the classroom to replace the previous one-way knowledge transfer process [36,37]. The new change also requires teachers to continuously improve their technical skills and teaching capacity in order to adapt to the development and changing times and to meet the increasing demands of students regarding classroom technology and environment [38].…”
Section: Landscape Architecture Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, due to insufficient visits and excursions, the effect of traditional landscape education is poor. Students aspire to have a new technology incorporated into the classroom to replace the previous one-way knowledge transfer process [36,37]. The new change also requires teachers to continuously improve their technical skills and teaching capacity in order to adapt to the development and changing times and to meet the increasing demands of students regarding classroom technology and environment [38].…”
Section: Landscape Architecture Educationmentioning
confidence: 99%
“…The development of VR also brings a great deal of enlightenment to landscape education. Greinert and Mrówczyńska's [36] study indicated that adopting modern educational technology can improve students' ability to solve landscape problems.…”
Section: Landscape Architecture Educationmentioning
confidence: 99%
“…For instance, Orietta Zanato Orlandini identified three principal functions of landscape in the classroom: (1) the hermeneutical function, where landscapes are read and their signs decoded, (2) the pragmatic function, where students learn to manage, plan and protect the territory and (3) social function, where students develop local identities while opening to "otherness," especially in contexts where there is increased migration [6]. Yet, it must be noted that current research on Landscape Education remain dominated by Euro-Western scholarly sources, ostensibly due to the ELC involving European countries [4,[7][8][9][10][11][12]. In European classrooms, Landscape Education has been weaved into the curriculum through, for example, including content in Social and Natural Sciences subjects which teach students about natural and anthropized landscapes [11]; drawings and questionnaires to get students to recognize the landscapes and around them and subsequently evaluate their views, experiences and feelings towards these landscapes [7,13]; through fieldwork trips to landscape sites [14]; and collaborative learning across multiple Universities, using technologically enhanced learning platforms to critically engage with the theories, methods, ethics and practices of participation in landscape planning [15].…”
Section: Introduction: Landscapes and Landscape Educationmentioning
confidence: 99%